Preservation of Kedidi Dance Values through Art Education: Social Roles and Strategies for Sustaining Cultural Continuity - M. Adha Al Kodri; Asyraf Suryadin; Rita Zahara (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
Kedidi Dance is a cultural heritage of the West Bangka community in the Bangka Belitung Islands, embodying strong social, spiritual, and aesthetic values. However, the rapid development of modernization has led to shifts in its social functions and a decline in interest among younger generations. This study aims to analyze the role of art education in preserving Kedidi Dance, examine its social functions within the community, and formulate strategies to sustain its existence amid social change. This research employed a descriptive qualitative approach through field study. Data were collected through observation, in-depth interviews, and documentation involving the leader and members of the Mawar Putih martial arts school, dancers, and community members in Benteng Kota Village, Tempilang District. The data were analyzed through stages of data collection, reduction, presentation, and conclusion drawing to identify patterns related to social roles and preservation strategies. The findings indicate that art education plays a significant role in transmitting cultural values and strengthening local identity through dance learning. Kedidi Dance has transformed from communal folk entertainment into a medium of cultural education and public performance while maintaining its core values. Preservation strategies include strengthening the social role of the institution, encouraging community involvement, allowing openness in artistic development, and building synergy with local government. Overall, art education and cross-sector collaboration are key factors in ensuring the sustainable and adaptive continuity of Kedidi Dance as a cultural identity in the modern era.